1992
DOI: 10.1007/bf03222322
|View full text |Cite
|
Sign up to set email alerts
|

The analytical modeling of normal grain growth

Abstract: A fundamental understanding of graingrowth phenomena provides a means to predict and control many of the observed material properties. This article reviews the development and present state of analytical theories of grain growth. The major geometric, dynamic, and statistical factors that must be considered in a rigorous formulation of grain dynamics are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the other hand, the microstructure during the growth phenomena consisting of stronger interactions that exist in chemisorbed systems normal grain growth and abnormal grain growth. In the usually result in a commensurate overlayer of atoms [6]. In normal growth, the microstructure exhibits a uniform inaddition to surface studies, similar superlattice structures have also been observed in intercalation compounds, where the large spacings between intercalant layers can result in quasi-two-dimensional behaviour.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…On the other hand, the microstructure during the growth phenomena consisting of stronger interactions that exist in chemisorbed systems normal grain growth and abnormal grain growth. In the usually result in a commensurate overlayer of atoms [6]. In normal growth, the microstructure exhibits a uniform inaddition to surface studies, similar superlattice structures have also been observed in intercalation compounds, where the large spacings between intercalant layers can result in quasi-two-dimensional behaviour.…”
Section: Introductionmentioning
confidence: 62%
“…crease in grain size whereas in abnormal grain growth the size of a few grains increases rapidly so that the normaSince the microstructure of materials plays an impor-lized grain size distribution is no longer time invariant tant role in physical and mechanical properties of enginee- [5,6]. ring materials, one of the major objectives of materials In other works experimental interest has focused on the science is controlling of the grain structure by grain defor-lattice structures observed for atoms that are adsorbed on mation, recovery, recrystallization, and grain growth in solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Under the effects of welding thermal cycle, atoms have enough mobility that make atoms move from deviation equilibrium position to equilibrium position, so that the internal stress and distortion energy will be relaxation gradually which result in recovery and recrystallization. At heat affected zone and near the weld junction, grain coarsening is serious and dislocation density decreases leading to a decline in hardness and strength [2][3][4][5][6].…”
Section: Failure Analysismentioning
confidence: 99%